Investigation of the effects of recycled aggregate concrete on the performance of reinforced concrete buildings - Alemdar, Zeynep Firat; Kurt, Yavuz Selim (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2022)
In this study, which examines the consideration of concrete (sustainable concrete) produced by using recycled aggregate in projected buildings as reinforced concrete frame or shear wall + frame systems, performance evaluation based on strain levels of buildings constructed with traditional concrete and sustainable concrete was made. Reinforced concrete buildings with eight floors and five-span assuming erected using 30% recycled aggregates or C30/37 strength class conventional concrete are examined according to Turkey Building Earthquake Code (TBDY 2018) by nonlinear pushover analysis. As a result of the analyses, the shear forces occurring at the floor levels in structural elements and the interstory drift ratios were determined. It has been observed that structures obtained from sustainable concrete provide the required performance against earthquake forces similar to the traditional concrete structures. Furthermore, it is proposed that a more elastic design should be considered especially in cases where the structure is built using recycled concrete by considering the differences in the production of concrete building material in Turkey Building Earthquake Code since recycled concrete shows more elastic behavior than conventional concrete.
Keywords: Pushover analysis; recycled aggregate; reinforced concrete frame building; shear wall system; performance evaluation; SEISMIC PERFORMANCE; STRENGTH; BEAMS; Engineering